2014
DOI: 10.1890/es13-00333.1
|View full text |Cite
|
Sign up to set email alerts
|

Implications of climatic heterogeneity for conservation of the Lesser Prairie‐Chicken (Tympanuchus pallidicinctus)

Abstract: Abstract. A geographic range is a heterogeneous matrix where the natural capability to support resident species varies from detrimental to optimal. Given this, the first priority for species conservation should be to determine where optimal environments exist. We used MaxEnt species distribution modeling to distinguish climatic characteristics associated with persistent leks from those at random locations in order to characterize the niche and potential distribution of the imperiled Lesser Prairie-Chicken (Tym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This hypothesis is supported by the fact that all male mortalities that occurred in June were in the drought years of 2009 and 2011. Our results corroborate similar findings presented in Grisham et al (2013) and Dunn and Milne (2014), which suggest that lesser prairiechickens in shinnery oak prairies live at the edge of their physiological tolerance for aridity, and that drought negatively affects the species through multiple mechanisms, including reduction of cover that protected the species from predators, as well as reduction in available food.…”
Section: Avianmentioning
confidence: 64%
See 1 more Smart Citation
“…This hypothesis is supported by the fact that all male mortalities that occurred in June were in the drought years of 2009 and 2011. Our results corroborate similar findings presented in Grisham et al (2013) and Dunn and Milne (2014), which suggest that lesser prairiechickens in shinnery oak prairies live at the edge of their physiological tolerance for aridity, and that drought negatively affects the species through multiple mechanisms, including reduction of cover that protected the species from predators, as well as reduction in available food.…”
Section: Avianmentioning
confidence: 64%
“…In particular, recent data are lacking on breeding season survival and causes and timing of mortality of lesser prairie-chickens in shinnery oak prairies. Shinnery oak prairies are semiarid grasslands, which experience hotter and drier environmental conditions compared with the rest of the species' distribution (Grisham et al 2013, Dunn andMilne 2014). Lesser prairie-chickens in this ecoregion are susceptible to drought, which results in inter-annual variation of nesting behavior (Grisham et al 2013(Grisham et al , 2014.…”
mentioning
confidence: 99%
“…We did not separate first nest from renests in this analysis because of the low sample size of renests. Our microclimate candidate models were developed using information presented in Flanders-Wanner et al (2004), Fields et al (2006), Grisham et al (2013), Dunn and Milne (2014), and Hovick et al (2014) that suggested temperature and humidity as limiting factors for various aspects of Holarctic grouse reproductive ecology. We also included several exploratory models that included the proportion of extreme temperature and VPD measurements to assess whether extreme microclimate conditions influenced nest survival (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We expected microclimate to influence nest survival similarly among the 3 ecoregions. We hypothesized that humidity would explain nest survival to a greater extent than other microclimate parameters for all 3 ecoregions (Grisham et al 2013, Dunn andMilne 2014). We expected nest survival probabilities to decrease as temperatures increased and humidity decreased across all ecoregions (Grisham et al 2013, Dunn andMilne 2014, Hovick et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation